Reconstruction of the Head and Neck Region Using Lower Trapezius Musculocutaneous Flaps - Soo Kwang Yoon; Seung Han Song; Nakheon Kang; Yeo-Hoon Yoon; Bon Seok Koo; Sang-Ha Oh (Archives of Plastic Surgery, 2012)
BackgroundRecent literature has indicated that free flaps are currently considered the preferred choice for head and neck reconstruction. However, head and neck cancer patients are frequently treated with chemoradiotherapy, which is often associated with a poor general and local condition, and thus, such patients are ineligible for free flap reconstruction. Therefore, other reconstruction modalities should be considered.MethodsWe used lower trapezius musculocutaneous (LTMC) flap based on the dorsal scapular artery to reconstruct head and neck defects that arose from head and neck cancer in 8 patients. All of the patients had undergone preoperative chemoradiotherapy.ResultsThere were no complications except one case of partial flap necrosis; it was treated with secondary intention. Healing in the remaining patients was uneventful without hematoma, seroma, or infection. The donor sites were closed primarily.ConclusionsThe LTMC flap is the preferred flap for a simple, reliable, large flap with a wide arc of rotation and minor donor-site morbidity. The authors recommend this versatile island flap as an alternative to microvascular free tissue transfer for the reconstruction of defects in the head and neck region, for patients that have undergone preoperative chemoradiotherapy.